Annotated catalogue of the click-beetle genus Elathous Reitter, 1890 (Coleoptera: Elateridae: Dendrometrinae), including habitus photographs for all species - Kundrata, Robin; Németh, Tamás; Prosvirov, Alexander S.; Hoffmannova, Johana (Zootaxa, 2021)
An annotated catalogue of the genus Elathous Reitter, 1890 (Coleoptera: Elateridae: Dendrometrinae) is presented. There are 48 species classified in the genus, of which seven are from the Nearctic realm, 39 from the West Palearctic from Morocco to Iran, and two from Japan. For each taxon we provide synonyms, information on type material, type locality, distribution, and bibliography.